Indigenous Planning: From Forced Assimilation to Self-determination. (February 2022) - Hibbard, Michael
Interest in Indigenous planning has blossomed in recent years, particularly as it relates to the Indigenous response to settler colonialism. Driven by land and resource hunger, settler states strove to extinguish Indigenous land rights and ultimately to destroy Indigenous cultures. However, Indigenous peoples have persisted. This article draws on the literature to examine the resistance of Indigenous peoples to settler colonialism, their resilience, and the resurgence of Indigenous planning as a vehicle for Indigenous peoples to determine their own fate and to enact their own conceptions of self-determination and self-governance.